Development and Implementation of a Computer-Based Information System for Recording Damaged Houses in Tangse District - Khairani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This study focuses on the development and implementation of a computer-based information system for recording house damage in Tangse District, an area frequently affected by natural disasters such as earthquakes, floods, and landslides. The system is designed to improve the efficiency and accuracy of managing damage data following disasters. The traditional manual data collection method has proven to be slow and prone to errors, slowing down response efforts. The research covers several stages, including needs analysis, system design, implementation, and evaluation. Microsoft Access 2007 was used for database management, and Microsoft Visual Basic 6.0 was utilized for the development of the user interface. Evaluation results confirm that the new system enhances data collection efficiency and accelerates the damage reporting process. It also improves coordination between agencies like the Regional Disaster Management Agency (BPBD), facilitating faster recovery efforts. The system developed can serve as a model for other regions with similar challenges in managing post-disaster data